Antibacterial assessment of Ziziphus mauritiana Lam on inhibition of the growth and biofilm of Streptococcus mutans - Syafriza, Dharli; Hasanah, Uswatun; Hidayatullah, Taufiqi; Rifki, Ayudia; Gani, Basri A. (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Streptococcus mutans (S. mutans) causes dental caries. S. mutans biofilms are inhibited by the antibacterial properties of Ziziphus mauritiana Lam (Z. mauritiana Lam). Purpose: Evaluating the potential of Z. mauritiana Lam in inhibiting the growth and biofilm formation of S. mutans ATCC 25175 in vitro. Methods: This study used the ethanolic extract of Z. mauritiana Lam as the test material and S. mutans as the research subject. Spectrophotometry (620 nm) was used to assess the growth of S. mutans, the inhibition of S. mutans biofilm using a 1% crystal violet staining was measured by spectrophotometry (520 nm), and the visualization of the biofilm mass was conducted with an electric microscope (200x). Results: At all concentrations, Z. mauritiana Lam displayed excellent growth inhibition of S. mutans 0.04–0.09 (< 300 CFU/mL) and was able to inhibit the formation of S. mutans biofilm with a strong scale of optical density (OD) 0.4 at 24 hours incubation time. At the same time, the incubation time of 48 and 72 hours tended to have moderate-scale biofilm inhibition (OD 0.2–3.9). At a concentration of 25%, the biofilm mass decreased by a relatively small size, the same as the positive control group. At 50%, 12.5%, and 6.25%, it was seen that the S. mutans biofilm mass experienced a dominant loss. Conclusion: Z. mauritiana Lam can be bacteriostatic against the growth of S. mutans and can inhibit the formation of biofilms by degrading the structure and mass of S. mutans biofilms.